Effects of Thermal Stress on Hepatic Melanomacrophages of Eupemphix nattereri (Anura) - De Souza Santos, Lia Raquel; Franco-Belussi, Lilian [UNESP]; Zieri, Rodrigo [UNESP]; Borges, Rinneu Elias; De Oliveira, Classius [UNESP] (Wiley-Blackwell, 2014)
Melanomacrophages are the pigmented cells present in the hematopoietic organs. Besides melanin, hemosiderin and lipofuscin are also observed in the melanomacrophages. For the liver, however, numerous studies relate these cells to immunological and metabolic functions. Therefore, the aim of this study is to evaluate the hepatic metabolism by quantifying melanin, hemosiderin and lipofuscin in the anuran Eupemphix nattereri submitted to varying thermal conditions. E. nattereri adult males were separated into three groups, as follows: (i) five animals in the control group were kept at room temperature (27 degrees C); (ii) 30 animals were submitted to hyperthermic (35.1 degrees C); and (iii) 30 to hypothermic (18.9 degrees) conditions. In each experiment, the animals were analyzed and separated into two different treatments: (1) immediately after undergoing the stress; and, (2) after recovering from the stress caused by the stimulus, at three distinct times (12 hr, 24 hr, and 48 hr). Both hyperthermia and hypothermia decreased hepatic pigmentation after thermal stress. The recovered animals of both experimental treatments showed as much pigmentation as the control animals. Thermal stress alters hemosiderin and lipofuscin as well, which may be related to liver function catabolism. In conclusion, liver pigmentation decreased due to temperature variation and duration of thermal stimulation to which the animals were exposed. The increase in temperature rather than hypothermia led to more drastic physiological disorders. In this study, we observed that thermal stress for a short period compromises the morphology and liver function, as observed by the changing pigmentation of melanomacrophages. These analyses can be used as biomarkers of environmental effects. Anat Rec, 297:864-875, 2014. (c) 2014 Wiley Periodicals, Inc.
Keywords: temperature; liver; pigmentation; anuran